2018
DOI: 10.1097/md.0000000000011329
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar pilocytic astrocytomas with spontaneous intratumoral hemorrhage in the elderly

Abstract: Rationale:Pilocytic astrocytoma (PA) is the most common pediatric central nervous system glial tumor. Adult occurrence is rare, especially in elderly adults. How to manage the pilocytic astrocytoma with spontaneous intratumoral hemorrhage in the elderly is still unfamiliar with clinician.Patient concerns:Reports of tumors with intratumoral hemorrhage in elderly adults are extremely rare. We report a case of a 62-year-old male diagnosed with cerebellar pilocytic astrocytomas with spontaneous intratumoral hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Previous reports have stated that the absence of pathological findings indicative of spontaneous hemorrhage is not uncommon. 6,13,19,24 As regards angiographic findings, Suzuki et al have reported the case of a diencephalic PA presenting with no vascular abnormality on DSA. 25 Although 1 case in this study presented with vascular abnormality on DSA, such cases would be relatively rare among hemorrhagic cases.…”
Section: Spontaneous Hemorrhage In Lggsmentioning
confidence: 99%
“…Previous reports have stated that the absence of pathological findings indicative of spontaneous hemorrhage is not uncommon. 6,13,19,24 As regards angiographic findings, Suzuki et al have reported the case of a diencephalic PA presenting with no vascular abnormality on DSA. 25 Although 1 case in this study presented with vascular abnormality on DSA, such cases would be relatively rare among hemorrhagic cases.…”
Section: Spontaneous Hemorrhage In Lggsmentioning
confidence: 99%
“…[ 18 , 24 ] Sixteen cases of cerebellar hemorrhage from PA with various clinical presentations have been previously reported. [ 2 - 5 , 7 , 9 , 10 , 13 - 15 , 18 - 20 , 22 , 23 , 25 ] [ Table 1 ]. The etiology of intratumoral hemorrhage in PA is unclear, but in the present case, the tumor tissue had abundant microvasculature with a glomeruloid-like appearance [ Figure 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilocytic astrocytoma is the most common primary brain tumor in pediatric population, comprising about 30% of all pediatric central nervous system tumors, 85% of all posterior fossa astrocytomas, and 10% of all cerebral astrocytomas in children. [1,2,4,7,8] The cerebellum, the brainstem, the optic nerve and chiasm, and the thalamus/ basal ganglia region are the most common locations of the lesion, with predilection within or near the midline sections. [2,5,8,9] Signs and symptoms commonly found in cerebellar pilocytic astrocytoma include headache, neck pain, vomiting, ataxia, and diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…[1] This tumor is a slow-growing neuroglioma, found among children and adolescents, usually located at the posterior cranial fossa, and has a classic imaging manifestation of a solitary, cyst-like mass with a strong contrast-enhancing mural nodule. [2][3][4][5] Multiple pilocytic astrocytomas in a single patient is a less common manifestation. [3,6] According to our knowledge, there has only been three publications on multiple involvement of pilocytic astrocytoma and 11 published articles on spontaneous intracystic hemorrhage in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%